The role of additive manufacturing in spare parts management: A systematic review - Wadhah Alzahmi; Abdulrahim Shamayleh; Marco Stefancich (Cleaner Engineering and Technology)
Recently, there has been significant focus on the use of advanced technologies in Spare Parts Management (SPM), signaling a notable shift towards more technologically advanced practices. Additive manufacturing (AM) offers numerous benefits, including enabling on-demand spare parts production, reducing inventory levels, shortening lead times, increasing flexibility for customized production, and minimizing downtime in maintenance processes. This work provides a systematic review, guided by the PRISMA framework, consolidating insights from 77 articles to deliver a comprehensive examination of the critical role that AM plays in SPM, while identifying potential research gaps. It begins with content analysis to evaluate existing AM-related studies within SPM highlighting key applications such as reverse engineering, decision-making frameworks, financial implications, intellectual property considerations, and regulatory concerns. Subsequently, a bibliometric analysis was conducted, underscoring the robust scholarly foundation and rapid expansion of AM-related research within this domain. The findings emphasize the significant capacity of AM to enhance SPM processes, reduce expenses, and improve overall supply chain operations. Future research should concentrate on achieving sustainability in AM material development, adhering to ethical manufacturing standards, ensuring rigorous quality control, enhancing design reliability, and fostering cross-industry collaboration. As SPM continues to evolve, it increasingly emphasizes balancing innovation with the adoption of sustainable, resilient, and globally standardized practices.